Postmastectomy radiation therapy and immediate autologous breast reconstruction: Integrating perspectives from surgical oncology, radiation oncology, and plastic and reconstructive surgery. Issue 3 (22nd October 2014) - Rochlin, Danielle H.; Jeong, Ah‐Reum; Goldberg, Leah; Harris, Timothy; Mohan, Kriti; Seal, Stella; Canner, Joe; Sacks, Justin M.
<x xml:space="preserve">Abstract</x> Background and Objectives The effect of postmastectomy radiation therapy (PMRT) on immediately reconstructed abdominal wall‐based tissue remains imprecisely defined. We evaluated evidence from all fields involved in care of the breast cancer patient in order to advance a unified recommendation regarding this therapeutic sequence. Methods We performed a MEDLINE and manual reference search to identify studies of PMRT with immediate autologous breast reconstruction. Inclusion criteria required studies to describe patients, flaps, and complication rates. Analyses were based on a random effects model. Surgical and radiation oncology literature was reviewed. Results Eleven retrospective studies of 337 patients with an average follow‐up of 18–60 months (out of 268 patients) were selected for inclusion. Overall rates of fat necrosis, revisional surgery, volume loss, and fibrosis/contracture ranged from 16.9% to 35.4%. One out of 260 patients experienced total flap loss. There was an increased probability of fat necrosis in the irradiated breast (OR = 3.13, 95% CI = 1.42–6.89, P = 0.005) among three studies with non‐irradiated controls. Five studies evaluated aesthetics with variable outcomes. Conclusions There is mixed evidence for the utility of PMRT with immediate autologous abdominal wall breast reconstruction. Further investigation requires prospective studies with collaboration among surgical oncologists, radiation oncologists, and plastic surgeons. J. Surg. Oncol. 2015 111:251–257. © 2014 Wiley Periodicals, Inc.